Effect of swim sprints on throwing accuracy and velocity in female collegiate water polo payers - Stevens, H. B; Brown, L. E; Coburn, J. W.; Spiering, B. A. (The Journal of Strength and Conditioning Research, 2010)
Swim sprints are a central component of water polo competitions; however, a paucity of data describes the effect of repeated swim sprints on game-like performances. Therefore, the purpose of this study was to investigate the effect of repeated swim sprints on water polo throwing velocity and accuracy. Eleven female community college water polo players (age: 18.91 ± 1.04 years, height: 165.91 ± 4.69 cm, and mass: 70.22 ± 15.36 kg) performed 2 conditions: control and sprint. The control condition consisted of 10 shots at the 5-m line, each with a 35-second rest period and aimed at a specific target on the goal. The sprint condition also had the same 10 shots but included a sprint between each throwing attempt. The sprints consisted of"head-down" swimming from the 2-m line to half court, then "head-up" swimming from half court to the 5-m line where the ball was shot and aimed at a specific target on the goal. Analysis was performed on ball velocity and accuracy between conditions. Ball velocity in the control condition (26.01 ± 3.13 mph) was significantly (p < 0.05) greater than the sprint condition (25.08 ± 2.76 mph); however, there was no significant difference in accuracy (shots made; Control: 3.00 ± 1.67; Sprint: 2.45 ± 1.03). These results indicate that ball velocity decreases in female collegiate water polo players after repeated swim sprints when compared with a control condition, yet accuracy is unaffected. Therefore, coaches should incorporate "game-like" conditions during practice that include repeated sprints-while focusing on maintaining high velocity to promote goal scoring.